Empirical Rates Characterization of Wearable Multi-Antenna Terminals for First-Responders - Estefania Crespo-Bardera; Mauricio Rodriguez; Matilde Sanchez-Fernandez; Eva Rajo-Iglesias; Rodolfo Feick; Reinaldo A. Valenzuela (IEEE Access, 2019)
Empirical characterization of the achievable rates for a wearable multi-antenna terminal shows the potential advantages of deploying a large number of antennas at the user end. We focus on the challenges and requirements of the broadband communication in future emergency communication systems, specifically addressing the outdoor–to–indoor propagation scenario, where the first responder is within an underground area such as a garage or basement. The measurement campaign undertaken characterizes the flat fading multiple-input multiple-output (MIMO) channel matrices at 3.5 GHz for a maximum of $M=30$ antennas deployed at the base station (BS), and $N=12$ wearable antennas at the user. The achievable rates are obtained for two transmission strategies that account for the different levels of channel knowledge. In both cases, all the MIMO processing is carried out at the BS.